Crystalline topological states at a topological insulator junction. (May 2019) - De Beule, C.; Saniz, R.; Partoens, B.
Abstract: We consider an interface between two strong time-reversal invariant topological insulators having surface states with opposite spin chirality, or equivalently, opposite mirror Chern number. We show that such an interface supports gapless modes that are protected by mirror symmetry. The interface states are investigated with a continuum model for the Bi 2 Se 3 class of topological insulators that takes into account terms up to third order in the crystal momentum, which ensures that the model has the correct symmetry. The model parameters are obtained from ab initio calculations. Finally, we consider the effect of rotational mismatch at the interface, which breaks the mirror symmetry and opens a gap in the interface spectrum. Highlights: The interface of topological insulators having opposite Chern numbers support gapless states protected by mirror symmetry. A continuum model for BiSe-like topological insulators is used, with model parameters based on ab initio calculations. Rotational mismatch at the interface breaks the mirror symmetry and opens a gap in the interface spectrum.